Prepoznavanje in evidentiranje mejic - Lampič, Barbara (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2021)
Hedgerows are a less-known element in the cultural landscape. In Slovenia, 4522 hedgerows are offi cially registered, covering a total length of 458.5 km. Due to various factors, their number and quality are decreasing. As a landscape vegetation feature that changes rapidly, their proper identifi cation and recording are paramount to their conservation and management. Using lidar-captured data, two approaches were de-veloped and evaluated for future applicability. We found that a suitable combination of methods, including geographic fi eldwork, is required for eff ective identifi cation and recording of hedgerows. In addition to methodologically appropriate and up-to-date recording, cross-sectoral coordinated actions and targeted awareness-raising among farmers and the general public on the multiple functions of borders in the cultural agricultural landscape will be crucial for the conservation of hedgerows.
Keywords: cultural landscape.; environmental protection; hedgerows; kulturna pokrajina; Ljubljansko barje; mejice; Slovenia; Slovenija; varstvo okolja